2010
DOI: 10.1182/blood-2009-03-212225
|View full text |Cite
|
Sign up to set email alerts
|

Heterozygous deletion of the PU.1 locus in human AML

Abstract: The transcription factor PU.1 is essential for myeloid development. Targeted disruption of an upstream regulatory element (URE) decreases PU.1 expression by 80% and leads to acute myeloid leukemia (AML) in mice. Here, we sequenced the URE sequences of PU.1 in 120 AML patients. Four polymorphisms (single nucleotide polymorphisms [SNPs]) in the URE were observed, with homozygosity in all SNPs in 37 patients. Among them, we compared samples at diagnosis and remission, and one patient with cytogenetically normal a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 23 publications
0
29
1
Order By: Relevance
“…Therefore, the cooperation between Sox4 and Sfpi1 haploinsufficiency in inducing myeloid leukemia is at least in part caused by a further decrease in Sfpi1 expression in myeloid progenitors because of direct transcriptional repression of the residual Sfpi1 allele by Sox4. Heterozygous PU.1 mutations have been found to be associated with some human AMLs 30,31 ; our results suggest that activation of SOX4 could be a mechanism to further downregulate PU.1 in these patients. Our identification of Sfpi1 as a repression target for Sox4 may also explain the Sox4-induced block of myeloid differentiation previously observed in 32Dcl.3 cells.…”
Section: Sox4 Cooperates With Reduced Sfpi1 Expression In Myeloid Leumentioning
confidence: 53%
“…Therefore, the cooperation between Sox4 and Sfpi1 haploinsufficiency in inducing myeloid leukemia is at least in part caused by a further decrease in Sfpi1 expression in myeloid progenitors because of direct transcriptional repression of the residual Sfpi1 allele by Sox4. Heterozygous PU.1 mutations have been found to be associated with some human AMLs 30,31 ; our results suggest that activation of SOX4 could be a mechanism to further downregulate PU.1 in these patients. Our identification of Sfpi1 as a repression target for Sox4 may also explain the Sox4-induced block of myeloid differentiation previously observed in 32Dcl.3 cells.…”
Section: Sox4 Cooperates With Reduced Sfpi1 Expression In Myeloid Leumentioning
confidence: 53%
“…Heterozygous inactivating mutations of the gene encoding human PU.1 (SPI1) have been identified in acute myeloid leukemia (AML) patients (Bonadies et al 2010;Link et al 2007;Mueller et al 2002). In addition, PU.1 expression is frequently suppressed in AML by the altered protein products of chromosomal translocations (Vangala et al 2003).…”
Section: Pu1 Levels and Disease: A Unified Perspectivementioning
confidence: 99%
“…Functionally critical decreases in PU.1 levels have been described in FLT3-internal tandem duplication (FLT3-ITD) (3), RUNX1-ETO (4), and promyelocytic leukemia (5), representing 24%, 7%, and 13% of all AMLs, respectively (cancer.sanger.ac.uk) (6,7). Additionally, PU.1 loss-of-function heterozygous mutations or deletions have been described in AML and are found in approximately 10% of MLL-translocated AMLs (8)(9)(10). Homozygosity of a single nucleotide variant in an upstream regulatory element (URE) of PU.1, lowering PU.1 expression, has been described in AML with complex karyotype (11), and a study on highly purified stem cells from patients with AML showed reduced PU.1 levels in at least 40% of examined cases (12).…”
Section: Introductionmentioning
confidence: 99%